Synergy of Indonesian National Armed Forces, Indonesian National Police, Government and Society in Flood Mitigation in the Kodim 0301 Area, Fast Labuh Baru, Pekanbaru - Zaini, Abdul Kudus; Kumalasari, Cyintia; Muttaqin, Muhammad Zainal (PT. Riset Press International, 2024)
The collaborative efforts involving the Indonesian National Armed Forces (TNI), Indonesian National Police (POLRI), government, and the local community in managing floods in Pekanbaru, Indonesia have been ongoing for an extensive period. These efforts require sustained attention, particularly during the prevailing rainy conditions. The military campaign approach comprises a series of joint operations executed to achieve strategic and operational objectives within specific spatial and temporal constraints. This military campaign involves Military Operations for War (MOW) and Military Operations Other Than War (MOOTW). The objective of this study was to describe and analyze the synergy among the Indonesian National Armed Forces (TNI), Indonesian National Police (POLRI), the government, and the local community in addressing floods in Pekanbaru through a military campaign strategy. This strategy involved TNI units with distinct branches and functions. The approach undertaken by the TNI (specifically those from KODIM 031 Pekanbaru) in flood disaster relief operations included collaboration with the Regional Disaster Management Agency of Pekanbaru to mobilize all available TNI and POLRI forces within the vicinity of Pekanbaru. This collaborative effort involved various stakeholders, such as TNI, POLRI, the government, NGOs, youth organizations (Karang Taruna), and other relevant entities. These activities took place in the East Labuh Baru, Payung Sekaki District, particularly along Arjuna Street. This effort is expected to establish an effective synergy among these groups, foster closer ties with the community, and manage floods by addressing issues related to drainage systems, canals, and overgrown vegetation.